Assessment of knowledge on non-pharmacological methods of pain relief during labour among nurses working in maternity and children hospital, Nepal - Dhakal, Amshu; Shah, Shrooti; Singh, Babita (Journal of Chitwan Medical College, 2017)
Background: Labor pain is a universal phenomenon and it is associated with the contraction of uterus. Rather than making the pain disappear with pharmacotherapy, the nurses can assist the laboring women to cope up with, build their self-confidence and maintain a sense of mastery of well-being. Thus, nurses must have knowledge to assess pain to implement pain relief strategies. Methods: A descriptive cross-sectional study was carried out among 52 nurses of Siddhartha Women and Children Hospital, Butwal, Nepal to assess Knowledge about Non-pharmacological Methods of Pain Relief during Labor using structured self-administered questionnaire. The reliability of the tool after pretesting was 0.883. Descriptive statistics was used to analyze the data. Results: Among 52 nurses, 36.5% were 18-22 years of age, 46.2% of them had qualification of Proficiency certificate level Nursing, 40.4% had experience of 3 years- 6 years. In this study, 46.2% had satisfactory knowledge about non-pharmacological methods of pain relief during labor, 32.6% had fair knowledge and remaining 21.2% had poor knowledge. Conclusion: This study concluded that less than half of the nurses had satisfactory knowledge about non-pharmacological methods of pain relief during labor. Since, there is an increased risk of complications resulting from pain and anxiety during labor, management of pain is very essential thus nurse’s knowledge on these methods is crucial. Hence, the nurses should be encouraged to enhance knowledge related to management of labor pain.